Potensi Industri Kreatif Dalam Mendiversifikasi Ekonomi Biru di Kepulauan Riau: Analisis Eksploratif - Hasrullah Hasrullah (Jurnal Archipelago, 2025)
This research discusses the potential of creative industries in diversifying the blue economy concept in the Riau Islands. The region's topography holds potential for sustainable marine resource utilization. Including through the creative industry which offers innovative approaches in its development. Few studies have integrated these two economic concepts, typically focusing on each concept separately as if there is a gap in their implementation. This research aims to explore the potential of creative industries that can be integrated into the blue economy concept. Using a qualitative approach with an explorative design through textual analysis of secondary data, the findings indicate that the creative industries and blue economy can jointly contribute to an inclusive and sustainable economy, aligning with regulations and the discourse on economic transformation strategies. Innovation across 17 creative industry subsectors could diversify the blue economy, particularly in the Riau Islands, considering four pillars of blue growth and three pillars of the Indonesia Blue Economy Index (IBEI). This includes advertising promoting ecotourism, architecture and crafts using sustainable marine materials, performing arts and fashion reflecting maritime culture, environmentally friendly product design, photography showcasing the beauty of the sea, and culinary offerings of sustainable seafood. Visual communication design, music, television, radio, publishing, film, animation, and video increase awareness about marine preservation. Sea-themed interior design supports tourism, and game-application development broadens maritime knowledge. The potential outlined in this research can evolve into business ideas and creative industry products, influence government policy, and lay the groundwork for further research in creative industry development strategies.